Effects of Congruent and Incongruent Stimulus Colour on Flavour Discriminations - Leonie Wieneke; Pauline Schmuck; Julia Zacher; Mark W. Greenlee; Tina Plank (i-Perception, 2018)
In addition to gustatory, olfactory and somatosensory input, visual information plays a role in our experience of food and drink. We asked whether colour in this context has an effect at the perceptual level via multisensory integration or if higher level cognitive factors are involved. Using an articulatory suppression task, comparable to Stevenson and Oaten, cognitive processes should be interrupted during a flavour discriminatory task, so that any residual colour effects would be traceable to low-level integration. Subjects judged in a three-alternative forced-choice paradigm the presence of a different flavour (triangle test). On each trial, they tasted three liquids from identical glasses, with one of them containing a different flavour. The substances were congruent in colour and flavour, incongruent or uncoloured. Subjects who performed the articulatory suppression task responded faster and made fewer errors. The findings suggest a role for higher level cognitive processing in the effect of colour on flavour judgements.